It’s what it is, tomorrow is another day! Interview with Angel Vianna (Urdimento: Revista de Estudos em Artes Cênicas, 2021)
Angel and Klauss Vianna are important researchers of the body and gesture in Brazil. Since the 1950s, with the School and the Ballet Klauss Vianna, in Belo Horizonte, they have influenced many generations, strongly contributing with the artistic and pedagogical fields. In this interview, Angel Vianna presents the highlights of her trajectory in dance and it's interface with theater and therapeutics, focusing on Grupo Teatro do Movimento, a dance company founded in Rio de Janeiro in the 70s and considered to be one of the first contemporary dance companies in the city. The text reveals Vianna’s thinking and her creative processes towards dance.
Keywords: Angel Vianna; Klauss Vianna; Dance; Interview; Grupo Teatro do Movimento